Fardhu'ain - Tuan Zainun Tuan Mat (Kota Bharu, Kelantan : Software Developers, 1999)
Rukun iman, rukun Islam, kisah rasul-rasul dan penerangan
System requirements: 486 and above, 16MB RAM, Windows 95 or 98 640 x 480 resolution, Sound Card, 16 bit colours (Hi-Colour)
Keywords: Islam -- Customs and practices; Youth, Muslim -- Religious life